2020
DOI: 10.1371/journal.pone.0234911
|View full text |Cite
|
Sign up to set email alerts
|

Clinical development success rates and social value of pediatric Phase 1 trials in oncology

Abstract: Objectives Drug development trials must fulfill social value requirement but no estimates of value provided by pediatric Phase 1 trials in oncology exist. These trials involve a particularly vulnerable population. Our objective was to assess of surrogates of social value of Phase 1 trials performed in pediatric oncology: rates of approval of tested interventions, transition to further phases of testing and citation in subsequent primary research reports. Methods We performed an analysis on a subset of eligible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…Seventeen of the 40 dose-finding studies transitioned from phase I to further stages (41%), similar to the 35% reported in other pediatrics reports, 43 and this proportion improved over time (33% v 45%).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Seventeen of the 40 dose-finding studies transitioned from phase I to further stages (41%), similar to the 35% reported in other pediatrics reports, 43 and this proportion improved over time (33% v 45%).…”
Section: Discussionsupporting
confidence: 78%
“…9 In agreement with ITCC recommendations, the majority of dose-finding trials (62%) incorporated expansion phase cohorts where additional safety, pharmacologic, and preliminary efficacy data could be collected, enabling the evaluation of biomarkers and response and the selection of new drugs for subsequent randomized trials (Table 3, Data Supplement, Table S1). Seventeen of the 40 dose-finding studies transitioned from phase I to further stages (41%), similar to the 35% reported in other pediatrics reports, 43 and this proportion improved over time (33% v 45%).…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, early phases of clinical trials also poorly predict phase III success. Therefore, surrogate measures should be considered only hypothesis-generating and not a marker of true clinical benefit [74][75][76][77][78].…”
Section: Discussionmentioning
confidence: 99%
“…Globally, it is estimated that there will be 13.7 million new pediatric cancer cases by 2050 [ 2 ]. Hence, new therapeutics that meaningfully improve outcomes in pediatric cancers are needed [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%